2004
DOI: 10.1074/jbc.m401687200
|View full text |Cite
|
Sign up to set email alerts
|

Horseradish Peroxidase Mutants That Autocatalytically Modify Their Prosthetic Heme Group

Abstract: The mammalian peroxidases, including myeloperoxidase and lactoperoxidase, bind their prosthetic heme covalently through ester bonds to two of the heme methyl groups. These bonds are autocatalytically formed. No other peroxidase is known to form such bonds. To determine whether features other than an appropriately placed carboxylic acid residue are important for covalent heme binding, we have introduced aspartate and/or glutamic acid residues into horseradish peroxidase, a plant enzyme that exhibits essentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 41 publications
(87 reference statements)
3
34
0
Order By: Relevance
“…In a separate work, Colas and Ortiz de Montellano [27] duplicated the ester link in horseradish peroxidase by incorporation of a glutamate residue close to the 3-methyl group (F41E variant of horseradish peroxidase) and also showed that the formation of the link was H 2 O 2 -dependent. A view has therefore emerged that any peroxidase, or perhaps any haem protein, that can react with H 2 O 2 and that has a suitable amino acid side chain poised in the right place will, under the right conditions, form a covalent link to the haem.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate work, Colas and Ortiz de Montellano [27] duplicated the ester link in horseradish peroxidase by incorporation of a glutamate residue close to the 3-methyl group (F41E variant of horseradish peroxidase) and also showed that the formation of the link was H 2 O 2 -dependent. A view has therefore emerged that any peroxidase, or perhaps any haem protein, that can react with H 2 O 2 and that has a suitable amino acid side chain poised in the right place will, under the right conditions, form a covalent link to the haem.…”
Section: Discussionmentioning
confidence: 99%
“…The result of enzymatic digestion and LC-MS analysis of the classic peroxidases with two covalent bonds (LPO, TPO, and EPO) is a 1,5-dihydroxyheme derivative. Mutation studies of heme proteins (horseradish peroxidase F41E, horseradish peroxidase S73E, LPO D225E, and LPO E375D) to investigate the autocatalytic nature and sequence of covalent bond formation have also led to non-native linkages at the 3-and 8-methyl positions (33,34). Because of single covalent bond formation in each mutant enzyme, once digested (trypsin/Pronase or proteinase K), each liberated heme co-factor was found as a monohydroxyheme (1-OH, 3-OH, 5-OH, or 8-OH) derivative.…”
Section: Design and Expression Of Soluble Duox1mentioning
confidence: 99%
“…Expression and Purification of the HRP F41E Mutant-The HRP F41E mutant was expressed and purified following modifications of the previously reported procedure (14). Viral stock was generated and amplified from single virus populations.…”
Section: Materials and Generalmentioning
confidence: 99%
“…Here we report the first direct and unambiguous evidence that the covalent links between the protein and the heme do, in fact, protect the heme from modification by HOX. HRP was engineered to introduce a covalent ester bond between the protein and the 3-methyl of the heme by mutating Phe 41 to a glutamic acid and pretreating the enzyme with low amounts of peroxide (14). The heme covalent bond is formed in essentially quantitative yield by this procedure.…”
mentioning
confidence: 99%